Too Much of a Good Thing? : Credit Booms in Transition Economies; The Cases of Bulgaria, Romania, and Ukraine - Duenwald, Christoph (IMF Working Papers; Working Paper ;, 2005)
Rapid credit growth in Bulgaria, Romania, and Ukraine has been driven by successful macroeconomic stabilization, robust growth, and capital inflows. While financial deepening is both expected and welcome, the recent expansions appear to have been excessive, as evidenced by widening current account deficits in Bulgaria and Romania, and prudential concerns in Ukraine. Policy responses have included attempts to both moderate credit growth and offset its impact on domestic demand, with mixed success thus far.